High Glucose Forces a Positive Feedback Loop Connecting Akt Kinase and FoxO1 Transcription Factor to Activate mTORC1 Kinase for Mesangial Cell Hypertrophy and Matrix Protein Expression - Das, Falguni (J Biol Chem, 2014)
High glucose-induced Akt acts as a signaling hub for mesangial cell hypertrophy and matrix expansion, which are recognized as cardinal signatures for the development of diabetic nephropathy. How mesangial cells sustain the activated state of Akt is not clearly understood. Here we show Akt-dependent phosphorylation of the transcription factor FoxO1 by high glucose. Phosphorylation-deficient, constitutively active FoxO1 inhibited the high glucose-induced phosphorylation of Akt to suppress the phosphorylation/inactivation of PRAS40 and mTORC1 activity. In contrast, dominant negative FoxO1 increased the phosphorylation of Akt, resulting in increased mTORC1 activity similar to high glucose treatment. Notably, FoxO1 regulates high glucose-induced protein synthesis, hypertrophy, and expression of fibronectin and PAI-1. High glucose paves the way for complications of diabetic nephropathy through the production of reactive oxygen species (ROS). We considered whether the FoxO1 target antioxidant enzyme catalase contributes to sustained activation of Akt. High glucose-inactivated FoxO1 decreases the expression of catalase to increase the production of ROS. Moreover, we show that catalase blocks high glucose-stimulated Akt phosphorylation to attenuate the inactivation of FoxO1 and PRAS40, resulting in the inhibition of mTORC1 and mesangial cell hypertrophy and fibronectin and PAI-1 expression. Finally, using kidney cortices from type 1 diabetic OVE26 mice, we show that increased FoxO1 phosphorylation is associated with decreased catalase expression and increased fibronectin and PAI-1 expression. Together, our results provide the first evidence for the presence of a positive feedback loop for the sustained activation of Akt involving inactivated FoxO1 and a decrease in catalase expression, leading to increased ROS and mesangial cell hypertrophy and matrix protein expression.